Mapping of Agro Tourism Potential in Misik Kalampangan Area using Unmanned Aerial Vehicle (UAV) Technology - Layang, Samuel; Perkasa, Petrisly (Talenta Publisher, 2021)
The people of the Misik Kalampangan area, which are located on peatlands, are not yet fully aware of the potential in their area. To turn this area into an agro-tourism, it is necessary to map the potential from the air using an aircraft (Unmanned Aerial Vehicle - UAV). This mapping process is also complemented by a direct observation survey in the Misik area with the aim of validating the results of visual interpretation of the resulting map product, so that the information conveyed on the map is in accordance with the conditions in the field. The product of this activity is a detailed scale photo map of the Misik area that can be used as the basis for land management planning in the Misik Kalampangan area. This activity was followed by the submission of photo map products which were attended by village officials and the community. Through this activity, the community is expected to be able to independently observe and update data on land cover changes and other phenomena that occur in the Misik area.